2021
DOI: 10.1155/2021/6682183
|View full text |Cite
|
Sign up to set email alerts
|

Identifying a Serum Exosomal-Associated lncRNA/circRNA-miRNA-mRNA Network in Coronary Heart Disease

Abstract: Background. Accumulating evidence supports the importance of noncoding RNAs and exosomes in coronary heart disease (CHD). However, exosomal-associated competing endogenous RNA- (ceRNA-) mediated regulatory mechanisms in CHD are largely unexplored. The present study aimed to explore exosomal-associated ceRNA networks in CHD. Methods. Data from 6 CHD patients and 32 normal controls were downloaded from the ExoRBase database. CHD and normal controls were compared by screening differentially expressed mRNAs (DEMs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…LncRNAs, miRNAs and mRNAs were involved in constructing miRNA-lncRNA-mRNA interaction network, which function critically in CVD. 19 Lin et al 20 reported that lncRNA THRIL relieved myocardial injury via miRNA-424/TXNIP/p53 aixs in CHD mice. Huang et al 21 confirmed that lnc-SLC15A1-1 upregulated CXCL10 and CXCL8 levels by sponging miRNA in HUVECs.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs, miRNAs and mRNAs were involved in constructing miRNA-lncRNA-mRNA interaction network, which function critically in CVD. 19 Lin et al 20 reported that lncRNA THRIL relieved myocardial injury via miRNA-424/TXNIP/p53 aixs in CHD mice. Huang et al 21 confirmed that lnc-SLC15A1-1 upregulated CXCL10 and CXCL8 levels by sponging miRNA in HUVECs.…”
Section: Discussionmentioning
confidence: 99%
“…Miao et al established a triple regulatory network of circRNA-miRNA-mRNA and found circ-YOD1 could be a good marker to predict the onset of CAD [ 39 ]. Mao et al constructed a serum exosome-associated ceRNA network to identify the promising diagnostic and therapeutic targets for CAD [ 40 ]. Ji et al performed RNA sequence analysis of circRNAs in peripheral blood mononuclear cells of patients with CAD and constructed a differentially expressed gene-circRNA-miRNA-mRNA network to identify dysregulated circRNAs involved in the pathogenesis of CAD [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A review has shown that [ 122 ] lncRNAs can regulate gene expression at the transcriptional, posttranscriptional, and epigenetic levels, thereby affecting the clinical course of the disease. Some studies have also demonstrated the key role of lncRNAs in disease development, and their role in heart development and heart disease is particularly prominent [ 123 , 124 ]. Until today, there have been no reviews on the underlying mechanism exploring the role of lncRNAs in diabetes inflammation.…”
Section: Othersmentioning
confidence: 99%